(untitled) (Journal of Forensic Medicine & Toxicology, 2023)
Consent law are developed from the intentional tort of battery, which protects the individual from unwanted physical touching of the body by one having neither express nor implied consent of the person touched. Written informed consent process is an underestimated part of surgery and neither surgeons nor patients sufficiently realize its importance. Many questionnaires and interview based studies have been done on knowledge, attitude and practice of clinicians about informed consent. In authors’ opinion, this is the first study in which actual consent documents were evaluated and analysed. In this study we have done retrospective study and evaluation of consent documents from case record of total 55 cases available in our department to identify any lacunae in the procedure and to provide recommendations for the same for improvement in practice. It can be safely concluded from the above-mentioned findings that, in actual practice, in majority of cases, consent taken is neither patient specific nor procedure specific. Sufficient disclosure of information about the disease and proposed treatment was also absent in majority of cases. Medical practitioners are not aware regarding the legal aspects of the consent document because in majority of cases consent was not directly taken